Efficacy of Tigecycline and Linezolid Against Pan-Drug-Resistant Bacteria Isolated From Companion Dogs in South Korea - Kim, Dong-Hyun; Kim, Jung-Hyun (Frontiers in Veterinary Science, 2021)
The emergence of multidrug-resistant bacteria in companion animals is an increasing concern in view of the concept of One Health. The antimicrobials linezolid (LZD) and tigecycline (TGC) are effective against multidrug-resistant bacteria isolated from humans; however, thus far, no previous study has evaluated the efficacy of these drugs against bacteria isolated from companion animals. This study aimed to evaluate the efficacy of LZD and TGC against bacteria that were isolated from companion dogs and showed resistance to all classes of antimicrobial agents. Clinical samples (auditory channel, eye, skin, and urine) were collected from dogs that visited the Veterinary Medical Teaching Hospital of Konkuk University (Seoul, South Korea) from October 2017 to September 2020. In total, 392 bacterial isolates were obtained, of which 85 were resistant to all classes of antimicrobial agents tested and were, therefore, considered potentially pan-drug resistant (PDR). The susceptibility of isolates to LZD and TGC was determined by the disk diffusion method and interpreted using the Clinical Laboratory Standards Institute guidelines. In total, 95.6% (43/45) and 97.8% (44/45) of gram-positive isolates were susceptible to LZD and TGC, respectively, whereas 82.5% (33/40) of gram-negative isolates were sensitive to TGC. In conclusion, both agents showed favorable efficacy, with the susceptibility rates for all potential PDR bacteria, except Pseudomonas spp., ranging from 72.7% to 100%. Thus, these drugs may serve as excellent antimicrobial options for veterinary medicine in the future.